Penyuluhan Pencegahan Stunting dengan PMT Melalui Produk Olahan Puding Buah Naga - Mertisa Dwi Klevina; Irma Mathar; Crismatoro Budi Saputro (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
Globally, stunting is one of the goals of the Sustainable Development Goals (SDGs). Indonesia is in the process of realizing the 2nd SDGs or sustainable development goals, namely ending hunger, achieving better food security and nutrition, and supporting sustainable agriculture. The target includes tackling the problem of stunting which is being sought to decrease by 2025. March 2023 Service Activities followed by 26 mothers. Implementation of community service activities used is Stunting Prevention Counseling with PMT. The method used is the lecture method, question and answer method and game/quiz. The result of this activity is to prevent stunting. Stunting can result in a decrease in intelligence (IQ), so that learning achievement becomes low and students cannot continue their studies. Some of the supporting factors for this activity include: 1. The participants have a great desire to obtain information and knowledge about socialization regarding reproductive health in preparation for breastfeeding, 2. This health education activity is strongly supported by the village, both directly and indirectly participating actively in the implementation of counseling.